Anodic stripping voltammetry of antimony at unmodified carbon electrodes - Lu, M; Toghill, K; Phillips, M; Compton, R (2013)
Antimony is an element of significant environmental concern, yet has been neglected relative to other heavy metals in electroanalysis. As such very little research has been reported on the electroanalytical determination of antimony at unmodified carbon electrodes. In this paper we report the electrochemical determination of Sb(III) in HCl solutions using unmodified carbon substrates, with focus on non-classical carbon materials namely edge plane pyrolytic graphite (EPPG), boron doped diamond (BDD) and screen-printed electrodes (SPE). Using differential pulse anodic stripping voltammetry, EPPG was found to give a considerably greater response towards antimony than other unmodified carbon electrodes, allowing highly linear ranges in nanomolar concentrations and a detection limit of 3.9 nM in 0.25 M HCl. Furthermore, the sensitivity of the response from EPPG was 100 times greater than for glassy carbon (GC). Unmodified GC gave a comparable response to previous results using the bare substrate, and BDD gave an improved, yet still very high limit of detection of 320 nM compared to previous analysis using an iridium oxide modified BDD electrode. SPEs gave a very poor response to antimony, even at high concentrations, observing no linearity from standard additions, as well as a major interference from the ink intrinsic to the working electrode carbon material. Owing to its superior performance relative to other carbon electrodes, the EPPG electrode was subjected to further analytical testing with antimony. The response of the electrode for a 40 nM concentration of Sb(III) was reproducible with a mean peak current of 1.07 μA and variation of 8.4% (n = 8). The effect of metals copper, bismuth and arsenic were investigated at the electrode, as they are common interferences for stripping analysis of antimony. © 2013 Copyright Taylor and Francis Group, LLC.